Case report: Five-year periodontal management of a patient with two novel mutation sites in ELANE-induced cyclic neutropenia - Lao, Zhentao; Fu, Jiarun; Wu, Zhiying; Zhu, Lihong; Wu, Shiwen; Lin, Yongheng; Hu, Chaoming; Duan, Dingyu; Wang, Panpan (Frontiers in Genetics, 2022)
Cyclic neutropenia (CyN) is a rare, ELANE-related neutropenia. Oral manifestations are among the initial signs of CyN and an important reason that leads patients to seek professional help. This case report describes a 12-year-old girl with recurrent oral ulcers, severe chronic periodontitis, and pathological tooth migration as the initial and main clinical symptoms of CyN. Two novel mutations in ELANE, c.180T>G (p.I60M) and c.182C>G (p.A61G) associated with CyN were observed. Bioinformatics research indicated lower stability and impaired molecular linkages of the mutant neutrophil elastase (NE) encoded by ELANE. However, the enzyme affinity to the classic substrate Suc–Ala–Ala–Ala–pNA was not substantially changed, suggesting that the impaired integrity and stability of the mutant NE, rather than catalytic deficiency, might be the pathogenic mechanism of ELANE mutation-induced neutropenia. The patient was prescribed scaling and root planing (SRP) and monthly periodontal maintenance without systemic management. Although the routine periodontal treatment was occasionally interrupted by the 2019 coronavirus pandemic, her periodontal devastation remained well-remitted in the 5-year follow-up assessment. The results of this study confirmed the importance of plaque control and proper diagnosis in the periodontal management of such patients and provide better clinical references. In addition, the novel mutations identified in this study expand the spectrum of known ELANE mutations in CyN and further contribute to knowledge regarding its pathogenic mechanism.